Historical understanding in the thought of Wilhelm Dilthey - Plantinga, Theodore, 1947- (Heritage., 1980)
Wilhelm Dilthey (1833-1911), a philosopher who has influenced twentieth-century intellectual history is subjected to careful analysis in this book. What emerges is a reinterpretation of his theory of understanding (Verstehen) and historical knowledge.